Properties of Glass-Fiber Hybrid Composites: A Review. Issue 5 (24th March 2017) - Singh, Jashanpreet; Kumar, Mandeep; Kumar, Satish; Mohapatra, S. K.
ABSTRACT: This paper provides a rigorous literature review in a field of glass-fiber composites. Glass-fiber composite is a type of fiber-reinforced polymer composites. Glass-fiber composite holds good properties such as low density, high strength, and easy processing, so widely used in aerospace, automotive, and construction. Fabrication of glass-fiber composite has been discussed in the present study. Combining the glass-fiber with other fibers into a single polymer matrix results in the development of hybrid glass-fiber composites. The hybridization in glass-fiber composites raised new ideas for future in the field of composites. GRAPHICAL ABSTRACT: